Tent use by artibeus and uroderma (Chiroptera, phyllostomidae) in Northern Colombia - Garbino, Guilherme S. T.; Rezende, Gabriela C. [UNESP]; Tavares, Valeria da Cunha (Sociedad Argentina para el Estudio de los Mamiferos, 2018)
During day roosts surveys for bats in the Parque Nacional Natural Tayrona, northern Colombia, we found occupied tents made of leaves of the palm species Sabal mauritiiformis and Cocos nucifera. We found Artibeus jamaicensis and Uroderma convexum using the tents, with groups of U. convexum ranging from 1 to 23 individuals, and a single occurrence for A. jamaicensis. A tent was simultaneously occupied by U. convexum and Thecadactylus rapicauda (Squamata). Although tent-roosting is known to be a widespread behavior for stenodermatine bats, these are the first observations of tent-roosting bats in northern Colombia and highlight a high potential for finding tent-using bats in the region.
Uso de tiendas de hojas por artibeus y uroderma (Chiroptera, phyllostomidae) en el norte de Colombia
Keywords: Cocos nucifera; Day roost; Sabal mauritiiformis; Stenodermatinae; Thecadactylus rapicauda